2010
DOI: 10.3855/jidc.834
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year surveillance of invasive Streptococcus pneumoniae isolates in central Turkey prior to the introduction of a conjugate vaccine

Abstract: Introduction: The aim of this study was to characterize the serotypes and antimicrobial susceptibility patterns of invasive Streptococcus pneumoniae isolates in central Turkey. Methodology: A total of 332 invasive S. pneumoniae isolates were identified, serotyped and tested for antimicrobial susceptibility by routine microbiological methods. Results: The most common serogroups/serotypes were 1, 19, 3, 18, 6, 14, and 7 in rank order. Serogroup/serotype coverage of the 23-valent polysaccharide vaccine, and the 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
2
14
0
4
Order By: Relevance
“…Perçin ve arkadaşlarının 15 S.pneumoniae serotip 1, sıklıkla lober pnömoni ve parapnömonik ampiyemli olgulardan izole edilen invazif bir suştur 1,7 . Ayrıca serotip 5, 7F (7A), 19A ve 3 ile birlikte KPA-7 ile aşılı popülasyonlarda da TKP'de en sık izole edilen serotiptir7.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Perçin ve arkadaşlarının 15 S.pneumoniae serotip 1, sıklıkla lober pnömoni ve parapnömonik ampiyemli olgulardan izole edilen invazif bir suştur 1,7 . Ayrıca serotip 5, 7F (7A), 19A ve 3 ile birlikte KPA-7 ile aşılı popülasyonlarda da TKP'de en sık izole edilen serotiptir7.…”
Section: Discussionunclassified
“…Uygun antibiyotik kullanımı, direnç gelişimini azaltabileceğinden, hastalardan izole edilen bütün suşların antibiyotiklere duyarlılık düzeyinin saptanarak antibiyograma göre tedavi verilmesi önerilmektedir. Penisiline dirençli pnömokok suşları, başka bir β-laktam grubundan olan ve penisilin ile aynı yoldan etki eden 3. kuşak sefalosporinlere karşı da yine benzer yolla direnç geliştirebil-mektedir 15 . Çoklu ilaç direncinin görülmesi, pnömokok enfeksiyonlarında optimum tedavi seçeneğinde belirsizliğe neden olmaktadır.…”
Section: Discussionunclassified
“…Russell et al (70) found that a minimum of two vaccinations before the age of 12 months, plus a PPSV23 booster at 18 months, was required for noticeable protection from S. pneumoniae to occur. While the PCV vaccines can be given at the same time as other infant immunizations, patient compliance in maintaining clinic visits can become difficult, even more so in developing countries (64). This multiple immunization schedule also requires a lot of vaccine product to be purchased, and this can quickly become expensive.…”
Section: Obstaclesmentioning
confidence: 99%
“…Unless these emerging capsule types are included in the current polysaccharide vaccines, no serotype-specific immune memory can be developed. Countries and regions of the world also vary in which S. pneumoniae serotypes are most prevalent in their reported cases of pneumonia and IPD (48,64). In these areas of the world, even if a full 3 dose PCV vaccination schedule is administered, the reduction in disease-causing strains may be 30-40 % less than in American clinical use (42).…”
Section: Obstaclesmentioning
confidence: 99%
See 1 more Smart Citation